From storage to delivery: Sperm volume and number of spermatozoa inside storage organs and ejaculates in males of Timogenes elegans (Scorpiones: Bothriuridae) - Vrech, David Eduardo (2018)
Sperm competition influences the evolution of many reproductive traits such as gonads, sperm or genitalia. Many sperm competition analyses concentrate in testes and ejaculates. Among arachnids, scorpions constitute an intriguing taxon for examining sperm production and usage. For example, in the family Bothriuridae the females of Timogenes elegans Mello-Leitaõ, 1931 accept more than one male per reproductive season and males produce spermatozoa continuously, storing them inside two elastic storage organs (i.e., two seminal vesicles plus two deferent ducts) before inseminating females, using a sclerotized spermatophore. In this study, we analyzed the sperm storage organs and the ejaculate volume transferred by T. elegans. We described the volume and number of spermatozoa at storage sites and in ejaculates, and investigated ejaculate volume and concentration in remating experiences. Storage organs varied in total size. Inside the spermatophore, the volume of the sperm drop represented 38% of the volume of both sperm storage sites. The remaining space around the sperm drop is filled with a gel-like substance. The ejaculate volume and spermatozoa number did not vary significantly between consecutive matings. Timogenes elegans stored abundant sperm inside the seminal vesicles. Available sperm was divided equally between both storage organs, and ejaculates were diluted in the spermatophore, presumably, with the gel stored in the trunk. There was no effect of body condition over any of the variables analyzed. Male sperm storage and ejaculate production are discussed considering the sperm depletion hypothesis and the sperm competition theory.